School Nurse Practices Related to Blood Pressure Screening, and Identification and Monitoring of High Blood Pressures in Youth. - Goulding, Melissa; Branley, Claire; O'Brien, Mary Jane; Hayman, Laura L.; Lemon, Stephenie C. (Journal of School Nursing, 2026)
Despite rising prevalence of high blood pressure among youth, literature on school nurses' practices related to youth blood pressure is limited. We aimed to describe school nurses' current practices related to blood pressure screening and identification and monitoring of high blood pressures. We conducted a web-based national survey of currently practicing school nurses and received 195 responses across 37 states. All participants reported having a blood pressure cuff, nearly all (98%) reported confidence measuring children's blood pressure, and 82% reported interest in doing more to support children's cardiovascular health. Blood pressure measurement by school nurses was common (73% reported "sometimes" or "often" and 25% reported "seldomly"). However, only 32% stated hypertension impacts their students and only 19% endorsed having enough time to complete all their necessary tasks. In describing school nurse's current practices related to youth blood pressure, we highlight opportunities for expanding this role and considerations for doing so.